ANALISIS PENGARUH PELAYANAN PRIMA DAN CITRA LEMBAGA TERHADAP LOYALITAS MELALUI MEDIASI KEPUASAN SISWA PADA LKP FIARA COMPUTER - Adelia Syahfitri Nasut; Zulkarnain Nasution; Meisa Nasution (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
This research aims to analyze the influence of excellent service and image institution on student loyalty and satisfaction on LKP Fiara Computer. The data which is used in this research is primary data collected from 52 respondents. The Sampling technique in this research is a non-probability sampling technique with pusposive sampling method, and analyzed by a non path analysis. The results of this research indicate that in structure of the I simultaneously excellent service and image institution significant affect student loyalty. Partially proven that excellent service and image institution significant effect on student loyalty. In the second structure, variable excellent service, image institution and loyalty simultaneous effect on student satisfaction. Partially excellent service, image institution and loyalty have a significant effect on student satisfaction. Analysis of the determinant coefficient (R2) on the first structure seen from R Square of 39%. This figure has the influence of excellent service and image institutions in loyalty simultaneously is 39.0%, while the remaining 61%. Analysis of the coefficient of determination (R2) in second structure seen from R Square of 52.1%. The lift has the influence of excellent service, image institution, and loyalty student simultaneously is 52.1%, while the remaining 47.9% (100% - 52.1%) is influenced by other variables. Keywords: Excellent Service, Institution Image, Student Satisfaction, Student Loyalty